Employees' perceptions on organizational socialization factors and its relationship to organizational culture - Kendren, Anak George (Universiti Malaysia Sarawak (UNIMAS), 2011)
Organizational socialization is a factor that can lead to perceived organization culture that is supportive. Organization socialization factors are training, understanding, co-worker support and future prospects. The understanding of the relationship between organization socialization and organizational culture is crucial in order for employees to be able to adapt or fit well into the organizational culture. This study was conducted to identifY the relationship between the employees' perceptions on organizational socialization factors and its relationship to the organizational culture. A survey research was conducted in an organization in public sector where 160 usable questionnaires were obtained from the survey. The outcomes of the Pearson Correlation Analysis showed that all of the organizational socialization factors were strongly correlated with the organizational culture. This means that the employees in the organization perceived that the organization culture was supportive in the provision oftraining program, assistance in employees understanding about their job responsibilities, satisfactory in co-worker support and the future prospects of the organization which are the rewards and recognitions. The contributions of this study were discussed as well as some recommendations were suggested.